Investigation of thermo-mechanical influences on fibre optic sensors using FEM simulation - Aswin Haridas (2016)
This dissertation aims at understanding the thermo-mechanical behaviour of the optical fibre sensors which are used nowadays in characterizing the strain and temperature behaviour of a system. The work followed in this report is a part of project HyMod, an initiative taken up by eminent institutions such as BMW & Lehrstuhl fur Leichtbau ^echnische Universitat Munchen) to develop next generation vehicle components aiming to increase the cost efficiency and reduce emissions. This project aims at creating and characterizing the structural requirements of a hydrogen fuel tank for the next generation fuel systems. The major requirement of such a fuel system would be a continuous health monitoring setup which provides non-ambiguous and transient response of system performance throughout the Iife of the vehicle. This could be achieved by fibre optic sensors based on the Rayleigh principle which could then provide continuous health monitoring for a distributed length/area. This thesis encompasses an analytical and finite element modelling approach to set up a base for comparison with the experimental observation. The first part develops a subjective analysis framework, which is used to reason the effectiveness of the approach chosen for analysis. The later part of the thesis defines and establishes the analytical and finite element method chosen to analyse the thermo-mechanical Ioad cases on specimen with integrated/embedded optical fibres. It has been observed that the behaviour of the fibre is more influenced by the host material used, rather than geometric changes developed in the model. The implicit analysis of carbon fibre specimen under thermal and tensile loads shows a strong complimentary nature towards embedment of the bare fibre for further tests. The implicit results obtained strongly agree with the mathematical model described while the trends followed in case of the explicit models and the experiment show good correlation.